Just add water solving the world's problems using its most precious resource - Larson, Rhett (Oxford University Press, 2020)
Scientists have long been searching for a unified field theory - one answer to all of the questions about the physical universe. In this book, I take a similar approach to social policy questions. What if we could find a unified social policy theory - the answer to every question from how to prevent war to how to promote gender equality? Most of our most serious global challenges are complex, multi-faceted 'wicked problems.' But perhaps the first step in solving wicked problems as seemingly distinct as racism and disease epidemics is the same: reform our laws, policies, and priorities to achieve global water security. Global water security means reasonable access for all people to water of acceptable quantity and quality with acceptable costs and risks. Just as the essential element to all life is water, so water is the essential element to solving life's challenges. Virtually every major social challenge - including gender inequality, racial discrimination, terrorism, space exploration, global disease epidemics, mass migrations, and climate change - has a significant and underappreciated water component. Each chapter of this book takes one of these wicked problems, illustrates the role water plays in that problem, and proposes reforms to address the water aspect of that problem, with the aim of achieving global water security. My goal in this this book is to convince the reader that the answer, or at least one part of the answer, to our most serious problems is the oft-repeated late-night infomercial exhortation - 'Just add water.'"--